Vocational training in the People's Republic of China : structures, problems and recommendations ; report - Münch, Joachim [Verfasser]; Risler, Matthias [Verfasser] (Office for Official Publications of the European Communities, 1987)
"This book is the result of two study-visits to China by the authors. It traces the historical and politcal background to present systems and structures of education in China today. It looks at the provision of vocational training for young people in schools and after school in apprenticeship or enterprises and the training of adults both in industry and in agriculture. Other chapters cover the training of trainers, those responsable for training, financing of training and some characteristics of the Chinese employment system. Finally, a number of recommendations are treated in some detail." (Verlag, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S System beruflicher Bildung; I 2.3.4 Asien; Berufsbildung; Entwicklung; Berufsbildungssystem; China